Antioxidative and quality properties of full-fat date seeds brew as influenced by the roasting conditions - Ahmed, Mohamed Fikry Mohamed; Yusof, Yus Aniza; Al-Awaadh, Alhussein M.; Abdul Rahman, Russly; Chin, Nyuk Ling; Mohd Ghazali, Hasanah (MDPI, 2019)
Full-fat roasted date seeds are considered an excellent source of antioxidants which can treat many diseases. The specific objectives were to investigate the effect of roasting temperature and time on the hardness of whole seeds, moisture content of the roasted date seeds powder, DPPH radical scavenging activity, total phenolic contents, extraction yield, pH, browning index and sensory properties of the brew prepared from the full-fat roasted date seeds and to construct descriptive models that could describe this effect. Date seeds were roasted at three temperatures (160, 180 and 200 °C) for different period of times (10, 20 and 30 min) using a natural conventional oven; then grinded and next brewed. Hardness of whole seeds, moisture content of the seeds powder, DPPH radical scavenging activity and total phenolic contents, extraction yield, pH and browning index and sensory properties of the brew were significantly affected by the roasting conditions. The statistical results indicated that the proposed model could adequately describe the measured properties. Strong correlations have been found among the properties of the brew as well. The producers of the date seeds brew can utilize these results for controlling the roasting process.